The Obstacles Faced by Indonesian TOEFL Test Takers - zahra, annisa; Ayu Dyah Anggraini; Dea Nirwanda Putri (Magister of English language Education study program, Universitas Muslim Nusantara Al Washliyah, 2023)
The Test of English as a Foreign Language (TOEFL) is an exam that determines whether a student whose nativelanguage is not English has strong enough English skills to succeed incourses at a college or university in theUnited States or Canada (S. Kim, 2021; Smart, 2019).This study aims to analyze test taker’s obstacles in TOEFLby Indonesian and specificly the researcher analyzes it with a English lecturer in University of Muslim Nusantara AlWashliyah, Medan. It is through answering the questionnare based on someone’s expertised. This research approachis qualitative method and a narrative approach with asking for five questions. Interviewis done through via messageas collecting data. The questions are Why do you need to study about TOEFL?, What do you have any obstacles duringstudying TOEFL?, After studying TOEFL, what are your wishes?, What is your motivation for studying TOEFL?, Howlong you study about TOEFL?. Based on the questions that is aksed by researchers, researchers hope that it is goingtobe as reflection for someone who wants to join up in TOEFL.Keywords: English Skills, Test Takers, TOEFL, Analysis